Chronic constipation: An unusual presentation of a Giant Serous Cystadenoma of ovary (Bangladesh Journal of Medical Science, 2013)
Benign ovarian cysts are fairly common. However, some of them may attain a large size and may prove to be malignant also. Here we report a case of 48 years old female presenting with chronic constipation due to a large ovarian cyst which was misdiagnosed on CT as mesenteric cyst. This case is being reported because of its large size, unusual presentation and missed diagnosis. DOI: http://dx.doi.org/10.3329/bjms.v12i1.11540 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.108-109